Aging-related skin microbiome in healthy Asian women - Dian Rahmayani; Winda Yulia; Zulkarnain Zulkarnain (Trends in Infection and Global Health, 2023)
The skin, an environment for the microbiome, has different physical, chemical and physiological states depending on the its site and the individuals. Because of these differences, the community and ecosystem of the microbiome are different for each individual. The differences in these microbiome ecosystems are also determined by their genetic properties, such as demographics, gender, age, race, level of hygiene, lifestyle, and physical injuries. Little is known about the association of microbiome and aging in Asian population. This review aim to gather current knowledge on aging-related skin microbiome in Asian women, namely Korean, Chinese and Thai. Changes in microbiome was found to be not only age-related but also ethnicity-associated. Future study with larger sample size is warrant to further elucidate the association of aging and skin microbiome in Asian female population.